Stress Intensity Factors for Circumferential Semi-Elliptical Cracks in Cylinders Subjected to Forced Convection Heat Transfer - S.M, Nabavi; Shahmorady, Mohammad B. (International Journal of Integrated Engineering, 2020)
This paper analyzes the circumferential semi-elliptical crack on the inner surface of a thick-walled cylinder while keeping the thermal loading in steady state. Forced convection heat transfer in the inner surface and free convection in the outer surface are applied to the cylinder, which was constructed from isotropic and homogeneous materials. To this end, the thermal stress intensity factors are determined using the weight function method. To validate the results, 3-D finite element method is applied as well as API standard code. Due to the existence of two planes of symmetry, only a quarter model of the cylinder was used and along the crack front, the modelling is carried out over singular isoparametric elements. The results for stress intensity factor are obtained at different aspect ratios and relative depths of the crack. The stress intensity factors calculated via built-in J-integral solver based on the domain integral technique in the ABAQUS software. The results obtained via this method were in good agreement with the proposed weight function, demonstrating the latter’s high adequacy and efficiency.